Governance and Performance in a "Marketized" Nonprofit Sector: The Case of German Care Homes. (February 2017) - Bode, Ingo
Nonprofit organizations are now involved in human service provision internationally. However, these organizations perform in variable ways that potentially undermine their public service function. Eldercare is a case in point. Drawing on various strands of organization theory and taking German care homes as an example, this article argues that differences in performance (concerning "input quality") may emanate from a distinctive mode of external governance that is crowding out capacity for quality-oriented internal governance. This is illustrated by evidence from an embedded case study. The findings hint at general problems with a "marketized" devolution of public services to nonprofits.